Healthy working time arrangements for healthcare personnel and patients: a systematic literature review - Vilde H. Bernstrøm; Daniele Evelin Alves; Dag Ellingsen; Mari Holm Ingelsrud (BMC, 2019)
Abstract Background A number of working time arrangements have been linked to negative consequences for both health personnel and their patients. A common hypothesis put forth to explain these findings suggests that certain working time arrangements lead to negative patient consequences due to the adverse impact they have on employee health. The purpose of this study is to use systematic reviews to investigate whether employee health explains the relationship between working time arrangements and patient safety. Methods A systematic literature review was performed including published reviews and original studies from MEDLINE, PsycINFO, Cinahl and Web of Science investigating working time arrangements for healthcare personnel, employee health and patient safety. In addition, we screened reference lists of identified reviews. Two reviewers independently identified relevant publications according to inclusion criteria, extracted findings and assessed quality. Results Six thousand nine hundred thirty papers were identified, of which 52 studies met our criteria. Articles were categorized into five groups according to how they approached the research question: 1) independent analyses of relationship between working time arrangements and employee health, and of working time arrangements and patient safety (5 studies); 2) relationship between working time arrangements on both employee health and patient safety (21 studies); 3) working time arrangements and employee health as two explanatory variables for patient safety (8 studies); 4) combinations of the above analyses (7 studies); 5) other relevant studies (5 studies). Studies that find that working time is detrimental to employee health, generally also find detrimental results for patient safety. This is particularly shown through increases in errors by health personnel. When controlling for employee health, the relationship between working time arrangements and patient safety is reduced, but still significant. Conclusions Results suggest that employee health partially (but not completely) mediates the relationship between working time arrangements and patient safety. However, there is a lack of studies directly investigating employee health as a mediator between working time arrangements and patient safety. Future studies should address this research gap.